First class - Wandsbeck, Seitz; Solomon, Abraham (1860)
Abraham Solomon's most well known paintings, originals in Southhampton Gallery, are two scenes on a train illustrating the aspirations of emigrants of a prosperous return following emigration. 'Second class' depicts the poor emigrants on the outward journey and 'First class' depicts a prosperous group of three passengers on their return journey. The original 'First class', painted 1854, is oil on canvas, 68.5 x 96.5 cm. with rounded top.
Inscription: 'First class' -- lower centre; 'Verlag u Druck v. Seitz Wandsbeck' -- lower right. [Translation: Edition and print from Seitz Wandsbeck]
Condition: Fair, tear lower left corner repaired by gluing sheet onto another and this sheet in turn is glued onto cardboard.
Title from inscription.
Also available online
Abraham Solomon, born 1824 in London, was a successful Victorian painter of contemporary social scenes. He also illustrated historical and contemporary literature. Solomon studied at the Bloomsbury School from 1824, entered the Academy Schools in 1839 and exhibited at the Academy from 1843. Solomon died in Biarritz, France in 1862.
Keywords: Railroad travel -- xPictorial works; Emigration and immigration -- Pictorial works